Psychotes Papi Kostick Web-Based Online - Mikael Duhantatya; Erdhi Widyarto Nugroho; Albertus Dwiyoga Widiantoro (Soegijapranata Catholic University, 2021)
Technological progress has experienced very rapid development. Technology that has developed began to slowly replace the conventional way of becoming more modern, especially in terms of psychological tests. The psychological test known as a psychological test is a test that is carried out to measure aspects of the individual psychologically. One of these psychological tests is the PAPI Kostick Test which is an inventory report of a person's personality in a work environment. The online PAPI Kostick test was developed using HTML, CSS, JavaScript, and PHP. Application testing was conducted to obtain correlation in terms of appearance, comfort, convenience, satisfaction, and long-term use.